INSTALLATION OF OMMAYA RESERVOIR IN A PATIENT WITH A PORENCEPHALIC CYST (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article describes a case of successful surgical treatment of a porencephalic cyst of the posterior horn of the left lateral ventricle and the installation of an Ommaya reservoir.